Effect of bone cement-reinforced pedicle screws combined with fusion repositioning therapy on lumbar spine function and postoperative complications in patients with severe lumbar spondylolisthesis - Jincai Tian; Hairong Zhang (Contemporary Clinical Trials Communications, 2023)
Objective: To retrospectively study the efficacy of bone cement-enhanced pedicle screws combined with interbody fusion reduction in the treatment of severe lumbar spondylolisthesis, its effect on lumbar function and complications. Methods: From January 2019 to June 2021, 82 cases of severe lumbar spondylolisthesis in our hospital were analyzed. According to the different treatment plans, the patients were divided into two groups: A and B, in which group A patients were treated with pedicle screws combined with fusion and reduction, and group B patients were treated with bone cement reinforced pedicle screws combined with fusion and reduction. Perioperative indexes, pain severity (VAS), Oswestry dysfunction index (ODI), and low back and leg pain score of Japan Orthopedic Association (JOA), spondylolisthesis reduction, intervertebral space height, intervertebral foramen height, complications, and screw loosening were compared between the two groups. Results: There was no significant difference in the amount of intraoperative bleeding between group A and group B (P > 0.05). The operation time of group B was longer than that of group A, and the hospitalization time was shorter than that of group A. The vertebral fusion rate of group B was higher than that of group A (P < 0.05). The VAS, ODI and JOA scores at the last follow-up in both groups were lower than those before surgery, and group B was lower than group A (P < 0.05). Compared with the preoperative period, the postoperative slippage degree grading improved in both groups, while the improvement rate in group B was higher than that in group A (P < 0.05). At the last follow-up, the scores of intervertebral foramen height and intervertebral space height in both groups were higher than those before operation, and those in group B were higher than those in group A (P < 0.05). There was no difference in the incidence of complications and screw loosening between the two groups (P > 0.05). Conclusion: Compared with conventional screw treatment, bone cement-reinforced pedicle screws combined with fusion repositioning can further improve the repositioning rate of slipped vertebrae in the treatment of severe LSL, while achieving a better intervertebral fusion rate. Therefore, the treatment of severe LSL with bone cement reinforced pedicle fusion and reduction is a safe and effective method.